On the Question of the Legal Nature of Planned Actsof State and Municipal Customers - Evgenii V. Solomonov; Aleksandr A. Iuritsin (Сибирское юридическое обозрение, 2017)
On the basis of evidence of individual acts, a suggestion is made on the legal property of planned acts of state and municipal (public) customers. The answer to the question indicated to better identify the legislation in the field of procurement to ensure the needs of the public in the framework of the rights of domestic industries.